Studi Problematika Pelaksanaan Pengajaran Bahasa Arab Dan Usaha Pemecahannya Di Madrasah Tsanawiyah Muhammadiyah 03 Sedayulawas Brondong Lamongan - Bahrus Surus, Lia Atiyah Rohmah (STIT Muhammadiyah Paciran, 2021)
This thesis aims to find out what problems are faced in teaching Arabic at Madrasah Tsanawiyah Muhammadiyah 03 Sedayulawas Brondong Lamongan, as well as to find out the efforts made in overcoming these problematics. The results obtained from this study are that there are probles in the implementation of teaching Arabic, naely: The Problem of students is that when receiving teaching 58%